2006
DOI: 10.1038/sj.onc.1209727
|View full text |Cite|
|
Sign up to set email alerts
|

Mutated telomeres sensitize tumor cells to anticancer drugs independently of telomere shortening and mechanisms of telomere maintenance

Abstract: Telomerase is a ribonucleoprotein complex that maintains the stability of chromosome ends and regulates replicative potential. Telomerase is upregulated in over 85% of human tumors, but not in adjacent normal tissues and represents a promising target for anticancer therapy. Most telomerase-based therapies rely on the inhibition of telomerase activity and require extensive telomere shortening before inducing any antiproliferative effect. Disturbances of telomere structure rather than length may be more effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 44 publications
(59 reference statements)
2
27
2
Order By: Relevance
“…Upon drug treatment, these cells showed a significant reduction in proliferative potential and revealed an increase in telomere length heterogeneity, even though the overall length of telomeres was maintained with no signal-free ends or chromosomal fusions, suggesting that the incorporated mutant repeats interfere with telomere structure maintenance and heighten tumor cells to harmful stimuli. 45 A similar process may occur in patients when only a single hTERC template is mutated. It is known that some proportion of patients with heterozygote telomerase allele would be at risk of exhausting the regenerative capacity of their marrow stem cells during adulthood, especially when challenged by environmental insults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon drug treatment, these cells showed a significant reduction in proliferative potential and revealed an increase in telomere length heterogeneity, even though the overall length of telomeres was maintained with no signal-free ends or chromosomal fusions, suggesting that the incorporated mutant repeats interfere with telomere structure maintenance and heighten tumor cells to harmful stimuli. 45 A similar process may occur in patients when only a single hTERC template is mutated. It is known that some proportion of patients with heterozygote telomerase allele would be at risk of exhausting the regenerative capacity of their marrow stem cells during adulthood, especially when challenged by environmental insults.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cerone and colleagues have demonstrated that a mutant template hTERC RNA can dictate the synthesis of aberrant telomeric repeats onto chromosome ends of human breast cancer cell lines with long overall telomeres. 45 Cells with the mutant repeats appeared to be more sensitive to anticancer drugs etoposide and doxorubicin. Upon drug treatment, these cells showed a significant reduction in proliferative potential and revealed an increase in telomere length heterogeneity, even though the overall length of telomeres was maintained with no signal-free ends or chromosomal fusions, suggesting that the incorporated mutant repeats interfere with telomere structure maintenance and heighten tumor cells to harmful stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cDNA was generated from total RNA and PCR was used to detect hTERT with primers HT1 and HT5 (Bodnar et al, 1998); mTERT with mTERT-WTF (5Ј-GACATGGAGAACAAGCTGTTTGCTGAG-3Ј) and mTERTshortR (5Ј-ATCTTGTATATATTGATGCAGACTGTCTGG-3Ј) primers; hTR with hTR-F3B and hTR-R3C primers (Nakamura et al, 1997); and mTR with mTR-F2-RT (5Ј-CCTAACCCTGATTTTCATTAGCTGTGGG-3Ј) and mTR-R2-RT (5Ј-GAGGCTCGGGAACGCGCGGTGGCCC-3Ј) primers. Human and mouse GAPDH was amplified with primers RT11 and RT12 (Cerone et al, 2006).…”
Section: Rna Isolation and Rt-pcrmentioning
confidence: 99%
“…Experiments carried out using human cell lines have also established an increased sensitivity to DNA damaging agents following inhibition of telomerase (Cerone et al, 2006a, b;Saretzki, 2003). Furthermore, when telomere integrity is compromised by expressing a mutant template RNA that results in repeats unable to recruit the shelterin complex, this also results in increased sensitivity to DNA damage (Cerone et al, 2006a). Increased drug sensitivity may occur before detectable telomere shortening (Masutomi et al, 2005), raising the possibility that telomerase may provide a protective function independent of its role in maintaining telomeric DNA arrays (Martinez & Blasco, 2011).…”
Section: Tmm and Drug Sensitivitymentioning
confidence: 99%